Optical coherence tomography in imaging of macular diseases - Figurska, Małgorzata; Robaszkiewicz, Jacek; Wierzbowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
OCT (opitcal coherence tomography), is a diagnostic method that enables the analysis of the retinal structures by means of high-resolution tomographic cross-sections of the retina. Whereas fluorescein and indocyanine angiography allow visualization of the retinal epithelium layer and chorioretinal vessels, OCT may help in diagnosing and monitoring the condition of many internal retinal layers. Ultrasound B-mode examinations have a resolution of about 150 μm while OCT provides a resolution of 10 μm. OCT makes it possible to detect and measure morphological changes, retinal thickness, retinal volume, thickness of retinal nerve fiber layer and various parameters of the optic disc. We use OCT in the analysis of the retinal structures in various pathologies such as macular holes and pseudo-holes, epiretinal membranes, macular edemas of various origins, including vasooclusive disease and diabetic macular edema, lesions of vitreoretinal interface and vitreoretinal traction, serous and hemorrhagic detachments of the retina and of pigment epithelium, age related macular degeneration, diabetic retinopathy, glaucoma. OCT is an examination that is fast, sensitive, reproducible, non-invasive, non-contact and easy to perform and interpret for a retinologist. The aim of this article is to present OCT principles and techniques as well as OCT interpretation and images of most common retinal diseases: age related macular degeneration – dry and wet form, retinal angiomatous proliferation (RAP), central serous chorioretinopathy, epiretinal membranes, macular holes, diabetic retinopathy.